2019
DOI: 10.1016/j.celrep.2019.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Functional Assessment of Lipoyltransferase-1 Deficiency in Cells, Mice, and Humans

Abstract: Highlights d Human LIPT1 mutations impair 2-ketoacid dehydrogenase lipoylation and activity d LIPT1 deficiency increases 2-HG and depletes structural lipids in plasma d LIPT1 deficiency impedes lipogenesis but increases fatty acid oxidation d LIPT1 regulates the balance between oxidative and reductive glutamine metabolism

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(75 citation statements)
references
References 51 publications
5
70
0
Order By: Relevance
“…7b). This preferential decrease in DLST lipoylation following ABHD11 loss argued against a general role for ABHD11 in lipoyl synthesis, and while it remained possible that ABHD11 was required for the final catalysis of DLST lipoylation, prior genetic studies suggested that LIPT1 was sufficient for this step [26][27][28] .…”
Section: Abhd11 Mediates Activity Of 2-og Dependent Dioxygenasesmentioning
confidence: 99%
“…7b). This preferential decrease in DLST lipoylation following ABHD11 loss argued against a general role for ABHD11 in lipoyl synthesis, and while it remained possible that ABHD11 was required for the final catalysis of DLST lipoylation, prior genetic studies suggested that LIPT1 was sufficient for this step [26][27][28] .…”
Section: Abhd11 Mediates Activity Of 2-og Dependent Dioxygenasesmentioning
confidence: 99%
“…The selective loss of lipoylated DLST following ABHD11 depletion initially suggested that it may be necessary for OGDHc lipoate conjugation. However, a requirement for ABHD11 in lipoate synthesis had not been previously observed 13,25,33 , and LIPT1 deletion or human loss of function mutations prevent PDHc and OGDHc lipoylation [25][26][27] . Instead, we found an absence of both the modified and unmodified lipoylated region of DLST by mass spectrometry (Figure 4b, c), consistent with the formation of a lipoyl adduct.…”
Section: Discussionmentioning
confidence: 99%
“…Lipoyl(octanoyl) transferase 2 (LIPT2), LIAS, and lipoyltransferase 1 (LIPT1) all reduced DLAT and DLST lipoylation in HeLa cells to a similar level, but only ABHD11 showed a selective loss of DLST lipoylation ( Figure S5b). This preferential decrease in DLST lipoylation following ABHD11 loss argued against a general role for ABHD11 in lipoyl synthesis, and while it remained possible that ABHD11 was required for the final catalysis of DLST lipoylation, prior genetic studies suggested that LIPT1 was sufficient for this step [25][26][27] .…”
Section: Abhd11 Prevents the Formation Of Lipoyl Adducts By Lipid Permentioning
confidence: 99%
“…In this reaction, its first step can synthesize R-2HG in the absence of IDH2 mutations. Thus, in patients with lactic acidosis, R-2HG (300 ng/mL vs. 200 ng/mL in healthy subjects) and to a greater degree (400 ng/mL vs. 100 ng/mL in healthy subjects) were elevated in plasma as well as in fibroblasts (119). When 2OGDH and/or lipoic acid synthase (LIAS) were ablated, both R-2HG and S-2HG were elevated, also due to the 2OG accumulation (19).…”
Section: Synergy Of 2hg-producing Enzymes With Other Enzymesmentioning
confidence: 90%
“…LIPT1 is essential for the lipoylation of PDH subunit E1, which forms acetyl CoA from pyruvate and thiaminepyrophosphate. Therefore, LIPT1 tunes the balance between the oxidative and reductive glutaminolysis (115,116), promoting the oxidative mode at a higher activity of LIPT1 (119). The ablation of LIPT1, such as in patients with lactic acidosis, causes a blockage of pyruvate oxidation by PDH, consequently increasing the pyruvate conversion to lactate and transamination of alanine with pyruvate by the aminotransferase reaction.…”
Section: Synergy Of 2hg-producing Enzymes With Other Enzymesmentioning
confidence: 99%